PEMBUATAN MINI GAME PADA GAME SIMULASI POLICE AGENT : TRAFFIC EDITION - Richen Richen; Jeanny Pragantha (Jurnal Ilmu Komputer dan Sistem Informasi, 2015)
Many traffic regulations have not known yet nor conveyed properly to public, especially about procedures and traffic laws. This information can be delivered through many ways, such as, a simulation game which is a game that simulating condition in real life. Police Agent: Traffic Edition is series of mini games containing simulation of procedures to get driving license, including theory and practice examination; traffic ticket, traffic trial, and traffic control. Each of the mini-games provide different informations. Police Agent: Traffic Edition created using ActionScript 3.0 and Adobe Flash. Key wordsSimulation Game, Police, Adobe Flash, Action Script, Traffic